Avaliação do manejo clínico da púrpura trombocitopênica imune dacriança: experiência do Serviço de Hematologia do Hospital das Clínicasda UFMG, no período de abril/1988 a dezembro/2001 - Raquel Baumgratz Delgado (2004)
Primary immune thrombocytopenic purpura idiopathic thrombocytopenic purpura or ITP is one of the most common acquired bleeding disorders of the childhood. Records of 187 patients followed up from April 1988 to December 2001 were analyzed retrospectively. The median age at diagnosis was 6.2 years (range from 2 months to 15.7 years) and the median time of follow-up corresponded to 1.4 years (range from 6 days to 12.1 years); 76% of the patients were either assymptomatic or had minor purpura. Only 9.2% of the patients had severe hemorrhagic episodes. Intracranial hemorrhage wasdiagnosed in one infant. Cutaneous bleeding alone was seen in 96% of the symptomatic cases. There was a association between the severity of the symptoms and the intensity of the thrombocytopenia. A total of 123 patients presented the acute form and other 51 had developed the chronic form. The insidious form of presentation, reported in 26.2% of cases, was associated with a larger number of splenectomies (p= 4x10-7) and with a reduced response to steroids (p= 0.003). As well as the lack of response to steroids (p<1 x 10-7), the insidious presentation was a predictive factor for chronicity (p= 1 x 10-7). About 25% of the patients were subjected to splenectomy. The response rate was 74,5%, with a median follow-up time of 21 months. Only one patient had postsplenectomy sepsis. Remission was the final result for80,2% of patients. Remission associated factors were male sex (p= 0.02), lower platelet number at diagnosis (p= 0.004), response to steroids (p= 0.003) and occurrence of a first remission (p< 1x10-7). Adhesion to international guidelines was not complete.